2019
DOI: 10.7120/09627286.28.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Post-natal development of EEG responses to noxious stimulation in pigs (Sus scrofa) aged 1-15 days

Abstract: This study examined electroencephalographic (EEG) indices of acute nociception in pigs (Sus scrofa) aged 1, 5, 7, 10, 12 and 15 days, post-natal. Ten pigs per age were anaesthetised with halothane in oxygen and maintained at a light plane of anaesthesia. EEG was recorded bilaterally using a five-electrode montage. Following a 10-min baseline period, tails were docked using side-cutter pliers and recording continued for a further 5 min. Changes in the median frequency (F50), 95% spectral edge frequency (F95) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Animals must be anesthetized before being subjected to EEG, but once the electrodes are in place EEG can provide an accurate reading of the brain activity irrespective of the movement of the subject. Currently, EEG has been particularly useful in measuring stress in animals [ 82 ] as well as responses to noxious stimulation [ 83 ]. Emotions in humans and non-human animals can be recognized through correlation from brain activity with the help of EEG signals [ 84 , 85 ] since EEG is also useful for emotion measurement, considering that it can be used on animals right up to the point of slaughter.…”
Section: Technologies For Measuring Animal Emotionsmentioning
confidence: 99%
“…Animals must be anesthetized before being subjected to EEG, but once the electrodes are in place EEG can provide an accurate reading of the brain activity irrespective of the movement of the subject. Currently, EEG has been particularly useful in measuring stress in animals [ 82 ] as well as responses to noxious stimulation [ 83 ]. Emotions in humans and non-human animals can be recognized through correlation from brain activity with the help of EEG signals [ 84 , 85 ] since EEG is also useful for emotion measurement, considering that it can be used on animals right up to the point of slaughter.…”
Section: Technologies For Measuring Animal Emotionsmentioning
confidence: 99%
“…Lambs-ontological changes in responses to castration [47,56]; Pigs-ontological changes in responses to tail docking [57], the noxious effects of castration with and without nerve blockade [46], the humaneness of intraperitoneal sodium pentobarbital injection as a killing method [58], postnatal changes in responses to noxious stimulation [59];…”
Section: Cerebrocortical Involvement In the Conscious Experience Of Pmentioning
confidence: 99%
“…An electroencephalographic (EEG) approach was developed to evaluate pain during tail docking (Kells et al, 2017a(Kells et al, , 2019. Indeed, changes in the EEG spectra under light anaesthesia could reliably indicate pain during surgical castration in horses (Murrell et al, 2003), sheep (Johnson et al, 2005) and pigs (Haga and Ranheim, 2005).…”
Section: Evidence Of Pain During and Shortly After Tail Dockingmentioning
confidence: 99%
“…Indeed, changes in the EEG spectra under light anaesthesia could reliably indicate pain during surgical castration in horses (Murrell et al, 2003), sheep (Johnson et al, 2005) and pigs (Haga and Ranheim, 2005). Changes in the EEG median frequency (F50) and 95% spectral edge frequency (F95), both indices of nociception, were reported in lightly anaesthetised piglets undergoing tail docking (Kells et al, 2017a(Kells et al, , 2019. When comparing pigs tail-docked at various ages and using different methods, these last authors concluded that tail docking within the first days following birth may be less painful than docking during the second or third week of postnatal life, and that tail docking using clippers may be more painful than using a cautery iron.…”
Section: Evidence Of Pain During and Shortly After Tail Dockingmentioning
confidence: 99%
See 1 more Smart Citation